Pengajaran Pemimpin Gereja Tentang Penyebutan Nama Yahweh Di Indonesia - Rinawaty Rinawaty (Sekolah Tinggi Teologi Injili Jakarta, 2021)
Teaching about the mention of Yahweh's name in Indonesia became a trending topic that very potential unsettling the Christian doctrinal order, so it needs Biblical theological analysis so that God's people can have a correct understanding and implement it well. It takes a qualified exegesis study to be accepted academically to be used as a reference or grip.Teaching church leaders about the mention of Yahweh's name is instruction or coaching from a spiritual mentor who has faith in Jesus Christ related to the calling, calling the God- respectful person with respect to Jesus Christ (Yahweh) and worshiped as the Savior, consisting of 5 (five) traits, namely: (1) The name YHWH is referred to as sacred in holy Places, (2) The name YHWH is referred to as the accompanying person, (3) The name YHWH is referred to as the god of Israel, (4) The name YHWH is mentioned in of worship, (5) The name YHWH is referred to as life giver.This research is conducted in Indonesia which is divided into three areas, namely: Western Indonesia, Eastern Indonesia and central Indonesia, starting from June 2018 until December 2019. The type of research used is an exportation of surveys and confirmatories. The population includes churches in Indonesia consisting of: Pastor/Shepherd, Assembly / Elders / deacons / head of departments, activist / coapers / volunteers, and the congregation, who assess spiritual leaders in the church. The type of sampling technique used is probability sampling, while the sampling technique utilizes stratified random sampling proposionate. Data collection technique used poll method, with Model Likert scale.The study found there were three hypotheses. The first hypothesis, church leaders tend to have taught maximally the mention of Yahweh’s name (Y) significantly at α0.05. The second hypothesis, the indicator of the name YHWH called Sacred in Holy Places (y1) is the most dominant indicator of forming church leaders ‘ teaching on the mention of Yahweh’s name (Y) significantly at α0.05. The third hypothesis, an indicator of the background category of respondents most dominant form the teaching of the church leaders on the mention of Yahweh’s name (Y) significantly at α0.05.